Implementasi Sensor Ultrasonik Untuk Menghitung Rakaat Shalat Berbasis Arduino Uno - Nur Azizah; Nana Sujana; Kunto Ajibroto (PT FORMOSA CENDEKIA GLOBAL, 2022)
Worship is an obligatory thing for us Muslims, especially prayer. The purpose of this study was to test the calculation of prayer cycles based on Arduino Uno. System Development Methods In this study the authors use prototype development starting from the communication stage to system testing. Researchers want to make a tool that can help us in worship, namely the implementation of ultrasonic sensors to count prayer cycles based on Arduino Uno, with a rakaat counter by ultrasonic sensors and the brain from this system by Arduino as input and output. After testing the tool, and the tool is functioning properly, the rak'ah counter will count when we do prostration. Then with a prayer schedule has been set.reminder it will sound according to the delay that.